Modulatory effect of Persea Americana oil against diethylnitrosamine-induced hepatotoxicity in rats: a proposed mechanism - Omayma A. R. Abozaid; Lobna M. Anees; Gehan R. Abdel-Hamed (Bulletin of the National Research Centre, 2021)
Abstract Background The purpose of this study was to investigate the effectiveness of Persea Americana (avocado) oil against diethylnitrosamine (DEN)-induced hepatotoxicity in rats. Methods For the induction of hepatotoxicity, DEN was administrated orally in a dose of 20 mg/kg B.wt for 6 successive weeks, and then the animals were gavaged with Persea Americana oil in a dose of 4 mL/kg b.wt. daily for another 6 weeks. Serum caspase-3 activity and poly (ADP-ribose) polymerase-1 (PARP-1) levels were estimated; in addition to gene expressions for NADPH oxidase, inducible nitric oxide synthase (iNOS), Bcl-2, and Bax were detected. Results The DEN-intoxicated group exhibited a remarkable increase in NADPH oxidase and iNOS expression combined with over-activation of PARP-1 and increased antiapoptotic Bcl-2 gene expression, whereas the expression of apoptotic biomarkers significantly decreased. On the other hand, treatment with Persea Americana oil significantly suppressed the elevated levels of hepatic enzymes and improved histopathological alterations in the liver. Furthermore, these groups displayed marked downregulation in NADPH oxidase and iNOS expressions. Persea Americana oil suppressed the expression of the antiapoptotic Bcl-2, activated the intrinsic mitochondrial apoptosis pathway through upregulation of pro-apoptotic Bax, and induced an obvious increase in caspase-3 activity. Moreover, Persea Americana oil administration markedly inhibited the activity of PARP-1. Conclusions This study indicated the promising potential of Persea Americana oil against DEN-induced hepatic injury through its anti-oxidative activity and pro-apoptotic effect via caspase activation and PARP-1 inhibition.